Association between craniofacial morphological patterns and tooth agenesis-related genes - Amanda Silva Rodrigues; Ellen Cardoso Teixeira; Leonardo Santos Antunes; Paulo Nelson-Filho; Arthur Silva Cunha; Simone Carvalho Levy; Mônica Tirre de Souza Araújo; Alice Gomes de Carvalho Ramos; Giuseppe Valduga Cruz; Marjorie Ayumi Omori; Mírian Aiko Nakane Matsumoto; Alexandre Rezende Vieira; et al. (SpringerOpen, 2020)
Abstract Background The aim of the present study was to assess if genetic polymorphisms in tooth agenesis (TA)-related genes are associated with craniofacial morphological patterns. Methods This cross-sectional, multi-center, genetic study evaluated 594 orthodontic Brazilians patients. The presence or absence of TA was determined by analysis of panoramic radiography. The patients were classified according to their skeletal malocclusion and facial growth pattern by means of digital cephalometric analysis. Genomic DNA was extracted from squamous epithelial cells of buccal mucosa and genetic polymorphisms in MSX1 (rs1042484), PAX9 (rs8004560), TGF-α (rs2902345), FGF3 (rs1893047), FGF10 (rs900379), and FGF13 (rs12838463, rs5931572, and rs5974804) were genotyped by polymerase chain reaction using TaqMan chemistry and end-point analysis. Results Genotypes (p = 0.038) and allele (p = 0.037) distributions for the FGF3 rs1893047 were significantly different according to the skeletal malocclusion. Carrying at least one G allele increased in more than two times the chance of presenting skeletal class III malocclusion (OR = 2.21, CI 95% = 1.14-4.32; p = 0.017). There was no association between another skeletal craniofacial pattern and some polymorphism assessed in the present study. Conclusion Our results suggest that the genetic polymorphism rs1893047 in FGF3 might contribute to variations in the craniofacial sagittal pattern.